Nonlinear Dynamic Characteristic Analysis of a Landing String in Deepwater Riserless Drilling - Jun Liu; Hongliang Zhao; Simon X. Yang; Qingyou Liu; Guorong Wang (Shock and Vibration)
The landing string is an important component of deepwater riserless drilling systems. Determination of the dynamic characteristics of the landing string plays an essential role in its design for ensuring its safe operation. In this paper, a dynamic model is developed to investigate the dynamic response characteristics of a landing string, where a landing string in a marine environment is modeled as a flexible slender tube undergoing coupled transverse and axial motions. The heaving motion of the drilling platform is taken as the upper boundary condition and the motion of the drilling bit caused by the interaction between the rock and the bit as the lower boundary condition. A semiempirical Morison equation is used to simulate the effect of the load imposed by the marine environment. The dynamic model, which is nonlinearly coupled and multibody, is discretized by a finite element method and solved by the Newmark technique. Using the proposed model, the dynamic responses of the displacement, axial force, and moment in the landing string are investigated in detail to find out the influences of driving depth of surface catheter, platform motion, bit movement, and marine environment on the dynamical characteristics of the landing string.